The Psychological Capital of Left-Behind University Students: A Description and Intervention Study From China - Liang, Li; Xiao, Qianguo; Yang, Yisheng (Frontiers in Psychology, 2018)
The migrant worker phenomenon in China has negatively impacted the psychological development of these workers’ children, whom researchers have termed “left-behind children” (LC) or university students with left-behind experience (USWL). Since USWL are the best among the LC in some sense, we decided to perform two investigations to determine if they might possess unique positive psychological capital factors. Study 1 aimed to explore the development of the psychological capital of USWL, and Study 2 utilized a group intervention design to improve USWL psychological capital. A questionnaire was administered to 281 USWL and 284 control university students in study 1. The results showed that the psychological capital of USWL was moderate, and their self-efficacy, optimism, hope, and overall psychological capital were significantly lower than those with no left-behind experience. However, their psychological resilience was remarkably higher than those who were not left behind. It also suggested that some demographic factors such as gender, grade, only child status, student leadership experience, reunion frequency with parents, and relationship with guardians significantly influence the psychological capital of USWL. In Study 2, a single-factor interventional experimental design based on the psychological capital intervention theory (PCI) was conducted in 73 USWL (38 in the experimental group, 35 in the control group). There were significant post-test differences between groups. Overall, our findings indicate that although the left-behind experience in childhood moderately impairs psychological capital development, it also fosters resilience. The psychological intervention based on PCI is an effective “remedy scheme” to improve their psychological capital qualities.